Nurses’ Perceptions of the Reasons of Medication Administration Errors, and Drug Administrations Practice in Multi-Centers South Sharqiyah, Oman - AL-Nasri, Amira Yahya; AL Bulushi, Ahmed Mansour (European Journal of Applied Sciences, 2022)
Background: Unsafe medication practices are the leading causes of avoidable patient harm in healthcare systems across the world. Nurses play a crucial role in the occurrence as well as preventions of medication administration errors. However, only a few relevant studies have thus far explored the problem in Oman. Objective: To identify reasons for medication administration errors (MAEs) among nurses and why nurses are not reporting drug administration errors. This study also aims to explore the current practice of drug administration among nurses. Method: Cross-sectional survey, using quantitative descriptive design. The study involved 290 randomly selected nurses from hospitals and primary health care settings, South Sharqiyah Governorate. The study used self-administered survey questionnaires, and the tool has been reviewed by experts from the same field of topic. The data will be analyzed descriptively and analytically using SPSS version 25. Results: The results indicated that only 31% of the nurses reported experiencing or involving in MAEs throughout their carrier, and the majority of nurses have a willingness to report the MAEs both self -errors 86.1% and errors made by others 81.9%. Nurses perceived that the most common reasons for MAEs where some drugs are look-alike (similar names or packing) 87.5%, heavy workload (74%), Verbal orders are used by physician (64.4%), physician change drugs order frequently (56.6%), nurses have limited information about drugs and calculation (56.2%), nurses fail to check the 10 rights of drug administration (56.2%), unfamiliar clinical setting to the nurse (55.9%) and Nurse has inadequate training in drug administration (55.5%). The most prevalent reasons for unreported MAEs included nurses fear of being punished or blamed (57%), and the patient or family might develop a negative attitude toward a nurse or the institution (55.9%). This study also found a significant relationship between reasons of medication errors and two variables: working institution (p=0.007), and duty shifts (p=0.001). Conclusion: MAEs is a serious problem that threatens patient safety. Staff training, non-punitive work environment and efficacious reporting system are the best solutions to prevent MAEs.